Monitoring Evaluasi Penerapan Sistem Pengembangan Manajemen Kinerja Klinis Di Rumah Sakit Tk. III Dr. Reksodiwiryo Padang : Monitoring and Evaluation of Performance Management Development System Implementation Clinical Performance Management Development System at Tk. III Dr. Reksodiwiryo Padang Hospital - Mona Ariestia; Yulihasri; Supiyah (NERS Jurnal Keperawatan, 2019)
The performance of nurses in service can be seen from the fulfillment of nursing characteristics, namely in nursing documentation. Good documentation requires monitoring and evaluation in accordance with performance management. The research objective is to determine the relationship between the implementation of Monitoring and Evaluation based on the Implementation of the Clinical Performance Management Development System (SPMKK) with the Implementation of Documentation. This type of research is quantitative research. The sampling technique used was simple random sampling of 83 nurses. Data analysis was used the univariate and bivariate statistics to see the relationship of dependent and independent variables using the Chi Square test. The results showed less than half (49.4%) of nurses were not good in monitoring activities based on SPMKK, (42.2%) nurses were not good enough in evaluating, (42.2%) nurses were not good enough to document nursing. The results showed a significant relationship between monitoring and evaluation activities with nursing documentation. For hospitals to implement evaluation monitoring so that nursing documentation runs smoothly in accordance with nursing procedures, the Head of nursing needs to improve the nurses' clinical performance skills with regular seminars.